Pandemic, Subjective Norms and Healthy Food - Kusdiyanto Kusdiyanto; Edy Purwo Saputro; Mabruroh Mabruroh; Sri Murwanti; Dewi Probowati Setyaningrum (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Research on the consumption of healthy food products is interesting because it is influenced by many factors. The respondents of this research involved 100 students of FEB UMS with the assumption that they are technology literate, the millennial generation, care about health, and have closeness to the intention to buy healthy food products. Hypothesis testing in this research uses regression analysis and the results show that attitude and behavioral control have a positive effect on purchase intention of healthy food products although subjective norms have no effect. The limitations of research findings become a reference for the development of further research